Analysis of Employee Performance Improvement Through Human Resource Development at the West Jakarta Development Sector Fire and Rescue Service Sub-dept. - Ahmad Hidayat; Joko Susilo; Ahmad Junaidi (JILPR Journal Indonesia Law and Policy Review, 2020)
The purpose of this research is to analyze and evaluate the factors affecting Employee Performance. This research uses qualitative approach with case study method. As for the informant is the user service and representative of officials in at the Dept. of Fire and Rescue Sector Kembangan, West Jakarta. The results of the study found that namely by following employees in various programs Education and Training and Courses, and for employees have been given the opportunity and opportunities as possible to follow the program development source power. Even employees are also given the opportunity to attend formal education to a higher level of education.